ETHNOMATIC EXPLORATION BASED ON REALISTIC ATHEMATICS EDUCATION (RME) IN TRADITIONAL GAME “LORE” - Anna Cesaria; Dewi Yuliana Fitri; Wahyudi Rahmat (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Ethnomatic is an interaction between mathematics with local culture. This study aims to explore ethnomatic on a traditional game called ‘Lore” in plane figure geometry learning. This is a qualitative study by using ethnography approach. The subjects of this research were elementary students who studied plane figure material by using a traditional game, Lore. The data were collected through observations, interviews, and documentations. The data analysis technique was by doing field observation then giving questions related to whatever the subjects did by using the game. On an abstract plane figure geometry learning, it could be applied into more concrete in the traditional game and also with Realistic Mathematics Education (RME). The findings showed that there was an ethnomatic on the traditional game, Lore in geometry learning especially on plane figure material (square, rectangle, trapezoid, and circle) based on RME. So, by having the relatedness it made the students knew the relationship of local culture based on RME and mathematics is an interrelated unit.Etnomatika merupakan interaksi antara matematika dan kultur budaya lokal. Penelitian ini bertujuan untuk mengeksplorasi etnomatika pada permainan tradisional “Lore” dalam pembelajaran geometri materi bangun datar. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan etnografi. Subjek penelitian adalah siswa Sekolah Dasar pada materi bangun datar dengan menggunakan permaianan tradisonal “lore”. Pengumpulan data dilakukan dengan obeservasi, wawancara dan dokumentasi. Teknik analisis data yaitu dengan cara melakukan observasi lapangan kemudian memberikan pertanyaan terkait apa saja yang dilakukan oleh subjek dengan menggunakan permainan tradisional “lore”. Pada pembelajaran geometri materi bangun datar yang abstrak dapat disajikan ke yang lebih konkrit dalam permainan tradisional dan juga dengan adanya Realistic Mathematics Education (RME). Hasil penelitian ini menunjukkan adanya etnomatika pada permainan tradisional “lore” dalam pembelajaran geometri khususnya bangun datar (persegi, persegi panjang, trapezium dan lingkaran) berbasis RME. Sehingga dengan keterkaitan tersebut membuat siswa dapat mengetahui bahwa hubungan kultur budaya lokal berbasis RME dan matematika merupakan salah satu kesatuan yang saling berkaitan.